FORMULASI DAN EVALUASI FISIK SALEP EKSTRAK ETANOL LENGKUAS MERAH (Alpinia Purpurata K Schum) TAHUN 2022 - Mustika, Rahayu (Journal of Pharmacy Tiara Bunda, 2023)
Malassezia furfur fungal infections on the skin can be caused by high temperatures and humidity, poor sanitation and hygiene. The risk of this disease if not treated is the presence of pigmentation spots that itch when sweating. Traditional treatment can be done using galangal rhizomes. This research aims to determine whether galangal rhizome extract is effective as an antifungal when formulated in a gel preparation. Extraction was carried out by maceration with 96% ethanol solvent. Phytochemical screening carried out includes tests for alkaloids, flavonoids, terpenoids/steroids, tannins, saponins, essential oils. The gel is made using carbopol base. The test method uses the disc diffusion method. The negative control used was a gel formulated without extract, while the positive control used was ketomed R gel. Next, an evaluation of the gel preparation was carried out. Based on the test results, the formulated gel was more effective as an antifungal than the extract as indicated by the formation of a clear zone of 22.67 mm. The results of data analysis between the extract, gel and positive control using the one-way ANOVA test showed a significance figure of 0.207 (p > 0.05), which means there was no significant difference between the extract, gel and positive control. Evaluation of the formulated gel meets the requirements for good physical properties of the gel, matches the skin's pH, and is safe when used on the skin